A Giant Scrotal Neurofibroma in a Child Masquerading as Filariasis: Uncommon Presentation of a Common Disease - Singh, Anurag; Singh, Gyanendra; Verma, Anuragani; Verma, Yogendra Narayan (Prague medical report, 2024)
Neurofibroma of the scrotum is a very uncommon benign neoplasm, specifically when it affects teenagers and is not associated with neurofibromatosis type I. To the best of our knowledge, only a couple of cases of neurofibroma in children have been documented. Here, we report a case study of a 17-year-old boy who had a giant scrotal lump for ten years masquerading clinically as filariasis. A provisional diagnosis of benign nerve sheath neoplasm was made based on cytology findings. The lump was surgically removed from the patient, and a histopathological and immunohistochemistry examination established the diagnosis of neurofibroma. The combined clinical, preoperative cytological, histological, and immunohistochemistry findings were not presented in the literature in any of the formerly documented cases of scrotal neurofibroma. The current case expands the spectrum of differential diagnoses for scrotal tumours that clinicians have previously observed.
Keywords: Nematode Infections; dítě; Neurofibromatosis 1; Adolescent; lidé; nematodózy; Filariasis; Neurofibroma; filarióza; Male; neurofibrom; neurofibromatóza 1; nádory mužských pohlavních orgánů; mladiství; skrotum; Child; mužské pohlaví; Scrotum; Genital Neoplasms, Male; Humans